Transmission Channels and Real Economy Effects of the Current Global Crisis on the Economies of Central East Europe - Johannes Stephan; Horst Brezinski (Verein für Socialpolitik, 2010)
This contribution analyses the real economy effects of the current global crisis in Central East Europe. It focuses on the transmission channels of a drying up of capital inflows, in particular on foreign direct investment inflows and on foreign currency borrowing, the current account, and the exchange rate regime. The analysis shows that the adverse real economy effects of the externally-driven capital inflow setback could be mitigated by a reduction of current account deficits, even though the latter depends on the flexibility of the exchange rate regime. Therefore, the countries with a fixed exchange rate to the Euro proved to be the countries in the region hit hardest. Next to these commonalities, the contribution also makes the case that in some cases, unsound national policies generated vulnerabilities that the crisis unveiled as non-sustainable and aggravated the real economy effects of this global crisis. Estonias construction and housing sectors are used here as a case in point. This contribution hence provides its own insights into the role of the exchange rate regime in the face of recurring financial crisis and in the run-up to Euro adoption, and argues that whilst there is very limited room for own national policies due to the external-biased growth and development strategy of the region, those were often unsound and aggravated the adverse effects of the global crisis on Central East Europe.
Keywords: E40; O20; P27; 330; Central East Europe; Estonia; Financial Crisis; Contagion; Real Estate; Housing